Mitochondrial Kinases and the Role of Mitochondrial Protein Phosphorylation in Health and Disease - Kotrasová, Veronika; Keresztesová, Barbora; Ondrovičová, Gabriela; Bauer, Jacob A; Havalová, Henrieta; Pevala, Vladimír; Kutejová, Eva; Kunová, Nina (Life (Basel, Switzerland), 2021)
The major role of mitochondria is to provide cells with energy, but no less important are their roles in responding to various stress factors and the metabolic changes and pathological processes that might occur inside and outside the cells. The post-translational modification of proteins is a fast and efficient way for cells to adapt to ever changing conditions. Phosphorylation is a post-translational modification that signals these changes and propagates these signals throughout the whole cell, but it also changes the structure, function and interaction of individual proteins. In this review, we summarize the influence of kinases, the proteins responsible for phosphorylation, on mitochondrial biogenesis under various cellular conditions. We focus on their role in keeping mitochondria fully functional in healthy cells and also on the changes in mitochondrial structure and function that occur in pathological processes arising from the phosphorylation of mitochondrial proteins.
Keywords: phosphorylation; disease; mitochondria; kinases